Study of the Drying Kinetics of Pears from cultivar D. Joaquina - Barroca, Maria João (2013)
Drying is one of the most widely used methods for preserving foods allowing extending their shelf life by minimizing the moisture content in the food so that the deterioration reactions will not be able to occur. The objective of the present work was to determine the drying kinetics of pears from cultivar D. Joaquina, and then use the experimental data to model the drying kinetics by means of different thin layer equations found in the literature. For that two temperatures were tested (60 and 70 ºC) and seven models were analysed. The results obtained allowed concluding that while some models were very adequate to predict the drying behaviour like Newton, Page, Modified Page, Henderson & Pabis and Logarithmic, others were not so good, such as Wang & Singh and Vega-Lemus.